The Effect of the Changes in Accounting Estimates of the Discount Rate to the Costs on Account of Creating Provisions - Anna Staszel; Artur Hołda (Nauki o Finansach)
The aim of the study is to answer the question of how a slight change in the actuarial assumptions (regarding the discount rate used) can affect the amount of the provisions, and consequently create the level of costs in the entity. In order to find the answer the financial statements of 148 stockexchange- quoted companies from 2007 to 2014 (1184 financial statements in total) were analysed, determining whether the changes in long-term provisions for retirement benefits provisions (due to the use of a different discount) have a significant impact on the financial statements of these companies. The research involved the use of deductive-inductive research methods in the form of literature review and analysis of the content of financial statements. The obtained results indicate that the estimation of the discount rate significantly affects the levels of costs related to creating provisions, which may be an effective tool for manipulating the financial result.(original abstract)